KOMITMEN INDONESIA PASCA LAND BASED SOURCES POLLUTION (LBSP) KAWASAN PANTAI NAIYANG PHUKET THAILAND TAHUN 2019 - Farhand Bima Anugrah T; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study explains the commitment of the Indonesian government after marine pollution by garbage originating from land to the Naiyang Beach area of Phuket, Thailand. This pollution is known as Land Based Sources Pollution. This incident received a response from the governments of Indonesia and Thailand. After confirming this through the Applied Oceanography Division of the Marine Research Center, the Indonesian Ministry of Maritime Affairs and Fisheries (KKP) ratified Presidential Decree No. 83 of 2018 in 2020, namely the National Action Plan (RAN) program. This study uses a Green Thought perspective in international relations and the level of analysis of the Nation State is supported by the International Cooperation Theory and this study uses the concept of The Good Neighborliness Principle. This research is a mixed research or Mixed Method with a documentary study research method. The scope of research is in 2019 to 2022 This research states that Indonesia continues to be committed to dealing with marine debris, especially in the Asean region with the National Action Plan (RAN) program “Reducing Marine Debris by 70% by 2025 or Free of Marine Debris by 2025” and encouraging the immediate implementation of the Bangkok Declaration on handling of marine debris which is expected to be legally binding. Keywords : Land Based Sources Pollution, Indonesian, Thailand, National Action Plan